The need of information systems (IS) integration complexity model for IS integration project - Arshah, Ruzaini Abdullah (Institute of Electrical and Electronics Engineers, 2008)
There is a need to address issues related to IS integration since integration are essential to organizations to move forward and supporting their business functions. However, there is no tool available to assess the complexity of IS integration, before thinking of measuring the success of integration initiative. If we can device a framework that depict the scenario of IS integration in organisation, it will be the first step to assist organisation understanding the IS integration status, whether they are on the right track, knowing what they are lacking of to proceed with integration, and whether they are using the right technology as solution to their integration problems. Thus, a construction of complexity model that depict the IS integration scenarios is proposed to assist in assessment of IS integration project.